(untitled) (Revista Española de Fisiología, 1987)
The conformational hen white egg lysozyme in the binary mixture water/Pb2+ as a function of the binary mixture composition has been studied.Intrinsic viscosity, partial specific volume and preferential adsorption parameter in the 0-0.100 M Pb2+ concentration range has been experimentally measured.The obtained results suggest that the observed conformational transition is a consequence of the interactions established between lysozyme and Pb2+ cation.